Directionality Effects of Aligned Wind and Wave Loads on a Y-Shape Semi-Submersible Floating Wind Turbine under Rated Operational Conditions - Shengtao Zhou; Baohua Shan; Yiqing Xiao; Chao Li; Gang Hu; Xiaoping Song; Yongqing Liu; Yimin Hu (Energies, 2017)
The Y-shape (triangular) semi-submersible foundation has been adopted by most of the built full-scale floating wind turbines, such as Windfloat, Fukushima Mirai and Shimpuu. Considering the non-fully-symmetrical shape and met-ocean condition, the foundation laying angle relative to wind/wave directions will not only influence the downtime and power efficiency of the floating turbine, but also the strength and fatigue safety of the whole structure. However, the dynamic responses induced by various aligned wind and wave load directions have scarcely been investigated comparatively before. In our study, the directionality effects are investigated by means of combined wind and wave tests and coupled multi-body simulations. By comparing the measured data in three load directions, it is found that the differences of platform motions are mainly derived from the wave loads and larger pitch motion can always be observed in one of the directions. To make certain the mechanism underlying the observed phenomena, a coupled multi-body dynamic model of the floating wind turbine is established and validated. The numerical results demonstrate that the second-order hydrodynamic forces contribute greatly to the directionality distinctions for surge and pitch, and the first-order hydrodynamic forces determine the variations of tower base bending moments and nacelle accelerations. These findings indicate the directionality effects should be predetermined comprehensively before installation at sea, which is important for the operation and maintenance of the Y-shape floating wind turbines.